The link between knowledge of the maternal diet and breastfeeding practices in mothers and health workers in Poland - Karolina Karcz; Izabela Lehman; Barbara Królak-Olejnik (BMC, 2021)
Abstract Background There are multiple misconceptions concerning the breastfeeding mother's diet and its adverse impact on breast milk composition and the breastfed child's health, which might lead to breastfeeding cessation. Although prophylactic maternal dietary restrictions are not recommended, mothers all over the world are often recommended to avoid certain foods, due to cultural beliefs, social pressure and even outdated or ambiguous medical recommendations. In Poland, there is no systematic approach to breastfeeding education in the form of nationwide educational programs for particular social groups. It was estimated that in 2017 only 3-4% of Polish infants were exclusively breastfed at 6 months of age. The aim of this study was to recognize the scale of common dietary misconceptions among lactating mothers in Poland and to compare knowledge and opinions between medical staff and mothers who have ever breastfed a child. In addition, the paper is an attempt to identify factors contributing to the still current practice of recommending prophylactic dietary restrictions to breastfeeding mothers by medical staff. Methods The study was conducted in Poland, in January - February 2019. The study used a diagnostic poll method and was conducted mainly in an electronic form. A total of 1159 completed questionnaires data were analyzed: 35.1% completed by medical staff and 64.9% by mothers in non-medical professions. Statistical calculations were conducted with Chi-square test, logistic regression and U Mann Whitney test (level of significance set at 0.05). Results The respondents presented a good level of knowledge and predominantly assessed the questioned statements correctly. Duration of breastfeeding was found to be the main factor determining respondents' knowledge (p <  0.05). Concerning medical staff, the parity (p <  0.001) and applying an elimination diet when themselves breastfeeding (p <  0.001) had a significant impact on recommendation of prophylactic dietetic restrictions to the lactating women. Conclusions Regardless of a resonably good level of knowledge on maternal nutrition in the lactation period, both breastfeeding mothers and medical staff are still convinced of the beneficial effect of preventive dietary restrictions, which affects further lactational counselling and lactational performance.